The Effect Of Profitability, Liquiduty, And Leverage On The Dynamics Of Construction Industry Share Price Listed On The Indonesian Stock Exchange For The Period 2019 -2023 - Dinda Suci Anggraini; Azizatul Munawaroh (UNIVED Press, 2025)
His study aims to analyze the effect of profitability, liquidity, and leverage on stock price dynamics in the construction industry listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The independent variables used include Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER), while stock prices are the dependent variable. This study uses secondary data from the published financial reports of construction companies. The analysis method employed is multiple linear regression. The results show that ROA has a significant negative effect on stock prices, indicating that the efficiency of asset utilization plays an important role in determining stock value. Meanwhile, CR shows a significant positive effect, reflecting the role of liquidity in maintaining the company's financial stability. DER, which represents the company's capital structure, also has a significant positive effect on stock prices. This study provides a theoretical contribution by expanding the understanding of the relationship between financial ratios and stock prices, particularly in the context of Indonesia's construction industry. Practically, the findings of this study can serve as a guide for investors in making investment decisions and for companies in developing more effective financial strategies.